Sustainability in the Textile Industry - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book examines in detail key aspects of sustainability in the textile industry, especially environmental, social and economic sustainability in the textiles and clothing sector. It highlights the various faces and facets of sustainability and their implications for textiles and the clothing sector.
Keywords: Mechanical Engineering; Industrial and Production Engineering; Industrial Chemistry/Chemical Engineering; Environmental Management; Characterization and Evaluation of Materials